2019
DOI: 10.1186/s12870-019-1786-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of MST, SUT and SWEET family sugar transporters in root parasitic angiosperms and analysis of their expression during host parasitism

Abstract: Background Root parasitic weeds are a major constraint to crop production worldwide causing significant yearly losses in yield and economic value. These parasites cause their destruction by attaching to their hosts with a unique organ, the haustorium, that allows them to obtain the nutrients (sugars, amino acids, etc.) needed to complete their lifecycle. Parasitic weeds differ in their nutritional requirements and degree of host dependency and the differential expression of sugar transporters is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 109 publications
0
21
0
Order By: Relevance
“…To identify MST genes in peanut, the predicted protein sequences were downloaded from PeanutBase (https ://peanu tbase .org) (Arachis duranensis V14167: A subgenome; Arachis ipaensis K30076: B subgenome; Bertioli et al 2016). The Sugar_tr domain (PF00083) (Deng et al 2019;Misra et al 2019) was identified using HMMER 3.0 program at a standard E value < 1 × 10 -5 . Conserved domain searches were performed against the conserved domain database in NCBI (https ://www.ncbi.nlm.nih.gov/Struc ture/cdd/wrpsb .cgi?).…”
Section: Identification Of the Mst Genes In Peanutmentioning
confidence: 99%
“…To identify MST genes in peanut, the predicted protein sequences were downloaded from PeanutBase (https ://peanu tbase .org) (Arachis duranensis V14167: A subgenome; Arachis ipaensis K30076: B subgenome; Bertioli et al 2016). The Sugar_tr domain (PF00083) (Deng et al 2019;Misra et al 2019) was identified using HMMER 3.0 program at a standard E value < 1 × 10 -5 . Conserved domain searches were performed against the conserved domain database in NCBI (https ://www.ncbi.nlm.nih.gov/Struc ture/cdd/wrpsb .cgi?).…”
Section: Identification Of the Mst Genes In Peanutmentioning
confidence: 99%
“…These data indicate that SWEET transporters may play important roles in mycoheterotrophic developmental stages as well as in adult plants of orchid species that rely on the mycorrhizal fungal symbiont for carbon (i.e., mycoheterotrophic and mixotrophic orchids). The role and localization of these different sugar transporters require further investigations, but it is interesting that several MST and SWEET transporters were also regulated during the parasitic interaction of plant species that directly obtain carbon from their host plants [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among those studied sugar transporter MONOSACCHARIDE TRANSPORTERS (MSTs) SUGARS WILL EVENTUALLY BE EXPORTED TRANSPORTER (SWEETs and SUCROSE TRANSPORTERS (SUTs). MSTs represents a large family of seven subgroups including EARLY RESPONSE TO DEHYDRATION (ERD6), SUGAR TRANSPORT PROTEINS (STP), PLASTID GLUCOSE TRANSPORTER (pGlcT), INOSITOL TRANSPORTERS (INT), VACUOLAR GLUCOSE TRANSPORTER (VGT), TONOPLAST SUGAR TRANSPORTERS (TST), and POLYOL/MONOSACCHARIDE TRANSPORTERS (PLT) [42][43][44]. Sucrose transporters' activities are strictly linked to the stimuli levels; their sensibilities enable plant adaptation to different external changes as small as it is such as temperature, drought, pathogen attack, saline, and other stresses.…”
Section: Structure and Isoforms Of Plant Inositol Transporter Genesmentioning
confidence: 99%